2012
DOI: 10.1099/mic.0.054320-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary mechanisms mediating aminoglycoside resistance in the multidrug-resistant Pseudomonas aeruginosa clinical isolate PA7

Abstract: The multiresistant taxonomic outlier Pseudomonas aeruginosa PA7 possesses the conserved efflux genes, mexXY; however these are linked to a unique gene encoding an outer membrane channel, dubbed oprA, that is absent in most P. aeruginosa strains. Using genetic knockouts and single copy chromosomal complementation, we showed that aminoglycoside resistance in PA7 is mediated in part by the MexXY-OprA pump, and intriguingly that MexXY in this strain can utilize either the OprA or OprM outer membrane channel, linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 77 publications
(121 reference statements)
3
59
1
3
Order By: Relevance
“…Expression of mexXY is controlled by the TFR MexZ and requires ArmZ (PA5471) (122), which interacts with MexZ (31,123). armZ encodes a homolog of RtcB, an RNA ligase involved in recovery from stress-induced RNA damage (124), and is cotranscribed with PA5470, which encodes a homolog of PrfH.…”
Section: Tfrs Involved In Regulating Multidrug Resistancementioning
confidence: 99%
“…Expression of mexXY is controlled by the TFR MexZ and requires ArmZ (PA5471) (122), which interacts with MexZ (31,123). armZ encodes a homolog of RtcB, an RNA ligase involved in recovery from stress-induced RNA damage (124), and is cotranscribed with PA5470, which encodes a homolog of PrfH.…”
Section: Tfrs Involved In Regulating Multidrug Resistancementioning
confidence: 99%
“…It has also been observed that in P. aeruginosa, the mexZ repressor gene upstream of mexXY-oprA in PA7 is mutated, leading to overexpression of mexXY-oprA. In addition, the effect of modifying enzymes was enhanced by the presence of this efflux pump to develop a high-level aminoglycoside resistance (Morita et al 2012).…”
Section: Rnd Efflux Pumpsmentioning
confidence: 95%
“…Nevertheless, AxyXY-OprZ confers a much higher level of resistance to aminoglycosides than MexXY-OprM in wild strains. It has recently been reported for some aminoglycosideresistant strains of P. aeruginosa that mexX and mexY are linked to the oprA gene in the same operon and that MexXY can utilize either OprM or OprA to form drug efflux complexes (18). Such an operon, including an oprA gene, has been also described in Burkholderia pseudomallei, a species intrinsically highly resistant to aminoglycosides due to expression of the AmrAB-OprA efflux pump (19).…”
mentioning
confidence: 99%